EFEKTIVITAS AVALIS PADA CALON NASABAH PEMBIAYAAN TERHADAP KELANCARAN PENGEMBALIAN PEMBIAYAAN - Cici Novitasari; Muhammad Wahyudi; Farida Anisah (Jurnal Education and Development, 2022)
This research was conducted to determine the application of avalis and the effectiveness of avalis on prospective financing customers on the smooth return of financing at the Harapan Syariah Cooperative in Surabaya. This type of research is a qualitative research with analytical methods with a deductive mindset to clarify the conclusions. This research was conducted by observing and interviewing the avalists and the Harapan Syariah Cooperative in Surabaya The results of this study conclude that the avalis in the Harapan Syariah Cooperative Surabaya has been effective. This is evidenced by the Harapan Surabaya Sharia Cooperative backlisting avalis and financing customers which causes the level of non-performing financing to continue to increase. Then the Harapan Surabaya Sharia Cooperative is looking for avalis and new financing customers in the hope that the level of non-performing financing will decrease. After a backlist was made to avalists and problematic financing customers, in 2017 the level of non-performing financing decreased, namely with an NPF of Rp. 123,000,000. then in 2018 it decreased again, namely with an NPF of Rp. 66,935,000. Meanwhile, the level of non-performing financing experienced a significant increase in the amount of Rp. 182,931,950 and decreased to Rp.123,000,000 in 2017. In 2018 there was a decrease in the level of non-performing financing, which was Rp. 66,935,000. Keywords: Effectiveness, Avalis, Financing